The unstructured C-terminal tail of the 9-1-1 clamp subunit Ddc1 activates Mec1/ATR via two distinct mechanisms - Navadgi-Patil, Vasundhara M. (2009)
DNA damage checkpoint pathways operate to prevent cell cycle progression in response to DNA damage and replication stress. In S. cerevisiae, Mec1-Ddc2 (human ATR-ATRIP) is the principal checkpoint protein kinase. Biochemical studies have identified two factors, the 9-1-1 checkpoint clamp and the Dpb11/TopBP1 replication protein as potential activators of Mec1/ATR. Here we show that G1 phase checkpoint activation of Mec1 is achieved by the Ddc1 subunit of 9-1-1, while Dpb11 is dispensable. However in G2, 9-1-1 activates Mec1 by two distinct mechanisms. One mechanism involves direct activation of Mec1 by Ddc1, while the second proceeds by Dpb11 recruitment mediated through Ddc1 Thr602 phosphorylation. Two aromatic residues, Trp352 and Trp544, localized to two widely separated, conserved motifs of Ddc1 are essential for Mec1 activation in vitro and checkpoint function in G1. Remarkably, small peptides that fuse the two Trp-containing motifs together are proficient in activating Mec1.